MAHMUD ZAMAKHSHARI'S "AL-KASHSHAF" AND "NUKATU- L-E'ROB" - Abzalova Farida (Bright Mind Publishing, 2025)
This article examines the scholarly contributions of Mahmud Zamakhshari, focusing on his prominent works "Al-Kashshaf," a renowned Quranic commentary (Tafsir), and "Nukatu-l-E'rob," a significant treatise on Arabic grammar and Quranic syntax. The study analyzes the distinctive features, similarities, and differences between these two works, highlighting Zamakhshari's expertise in both exegesis and linguistics. Furthermore, it explores the influence of Mu'tazili philosophical thought on "Al-Kashshaf" and the methodological approaches employed by Zamakhshari in interpreting the Quranic text. The analysis demonstrates the enduring significance of these works as valuable resources for understanding the Quran and the Arabic language.
Keywords: Mahmud Zamakhshari, Al-Kashshaf, Nukatu-l-E'rob, Tafsir, Quranic Exegesis, Arabic Grammar, Syntax, Mu'tazili, Islamic Scholarship, Linguistics.